Agenda 2030 and human rights: an analysis of the Ibero-American Literature in Library and Information Science - Santos, João Carlos Gardini; Martínez-Ávila, Daniel; Gomes De Mello, Mariana Rodrigues [UNESP] (Ibersid, 2022)
The 2030 Agenda of the United Nations (UN) presents 17 Sustainable Development Goals (SDG) that can be used as a theoretical framework in scientific research. In this sense, our research question is as follows: is there a corpus of published literature in Portuguese or Spanish in the area of Library and Information Science and with an explicit mention to human rights that can be used as a theoretical reference and basis for future research on at least one of the 17 SDGs proposed by the UN in the 2030 Agenda? To answer this question, we conducted a search in the specialized database Library and Information Science Abstracts (LISA) and then analyzed and categorized the retrieved documents using a methodology based on Bardin. The results show that after the publication of the SDGs there was a significant increase in scientific publications on sustainable development in line with human rights. SDG number 16, “Promote just, peaceful and inclusive societies” is the one with the highest number works on human rights. We conclude that there is a corpus of research on sustainable development in Library and Information Science that recognizes its importance and can be used as a background for future research dealing with any of the SDGs.
Agenda 2030 y derechos humanos: análisis de la literatura iberoamericana publicada en ciencia de la información
Agenda 2030 e Direitos Humanos: análise da literatura iberoamericana publicada em Ciência da Informação
Keywords: Agenda 2030; Human rights; Iberoamerica; Sustainable Development Goals